3D enabled facile fabrication of substrates with human tongue characteristics for analysing the tribological behaviour of food emulsions. (October 2021) - Fan, Juan; Annamalai, Pratheep K.; Prakash, Sangeeta
Abstract: The mouth-feel or oral perception of a food may vary in different oral surfaces or tongue-palate environment depending on the physical characteristics of human tongue. Tribological measurements emulating the characteristics of tongue-palate environment will assist in the evaluation of oral perception of food materials. This study reports a 3D printing assisted approach for rapid fabrication of the soft elastomer substrates with different surface (roughness) and bulk characteristics (elastic modulus and thickness) for tribological measurements. The influence of substrates with various regularly patterned surfaces, elastic modulus, and thickness on the lubrication properties of four food emulsions (full-fat and skim milk, high-fat and low-fat yoghurt) has been investigated. It is observed that friction coefficient of food emulsions increases with a decrease in height or an increase in density of rectangular micro-scale pillars representing papillae on the surface of soft substrate. Interestingly, a decrease in the elastic modulus of the substrates causes an increase in the friction coefficient for the milk samples, whereas for yoghurt samples it causes a decrease. The variations in the thickness of the substrates have little effect on the friction coefficients of the food emulsions. Graphical abstract: Unlabelled Image Highlights: Moulds for fabrication of soft elastomer substrates are 3D printed Modulation of the bulk and surface characteristics of substrates was achieved Papillae height and density on the substrate influenced the friction coefficient of emulsions An increase in elastic modulus of substrates reduced the friction coefficient of milk. Substrate thickness had little effect on the friction coefficient of the emulsions.